Field and laboratory assessment of larvicidal activity of tobacco plants and the cigarette butt waste on Culex pipiens (Linnaeus, 1758), Aedes aegypti (Linnaeus, 1762) L. and non-target organisms - Mohamed M. Baz; Yasser A. El-Sayed; Samah Abdel Gawad; Mohammed E. Gad; Moustafa Ibrahim; Mohammed H. Alruhaili; Hattan S. Gattan; Reham M. Mostafa; Sarita Kumar; Ibrahim E. Hussein; Abdelfattah Selim; Abeer M. Alkhaibari; et al. (PLoS ONE, 2025)
Mosquitoes are the primary vectors that transmit diseases affecting humans. Chemical interventions for mosquito management have caused harm to humans, beneficial organisms, and the environment. Hence, researchers are diverting their interest to comparatively safer botanicals. The tobacco plant ( Nicotiana tabacum L.) is known to contain nicotine and other diverse bioactive phytochemicals with insecticidal properties. The current study aims to repurpose nicotine-containing cigarette butt waste (CBW), a widespread environmental pollutant that poses ecological and economic challenges due to its persistent and toxic chemical components, as friendly insecticides. The study evaluated the methanol and aqueous extracts from tobacco leaves ( Nicotiana tabacum L.) and cigarette butts (CBs) of various brands against the larvae of Culex pipiens and Aedes aegypti under field and laboratory conditions and their effects on non-target organisms. Tobacco leaves methanol extracts exhibited higher larvicidal activity (98.0–100%, at 500 ppm) than aqueous extracts (96.0–100%, at 2000 ppm). The methanol extracts of Merit CBs (LC 50 = 15.45 ppm) demonstrated greatest effectiveness against Cx. pipiens larvae, while the methanol extracts of Cleopatra CBs (LC 50 = 25.71 ppm) were found to be more effective against Ae. aegypti 24 hours post-treatment. On the other hand, the aqueous extracts of LM cigarette butts (LC 50 = 61.22 and 68.14 ppm) were recorded as most potent against Cx. pipiens and Ae. aegypti larvae than other CBs. Interestingly, the oviposition activity was higher and positive in CB-treated blackish color cups than that in control water. Field trial data showed 95% and 84% larval reduction with respective Merit CB and tobacco leaves methanol extracts 24 h post-treatment, with persistence for 6 and 3 days, respectively. GC-MS analyses showed a higher number of terpenes, flavonoids, and phenolic compounds in CB extracts. The 3-(1-methyl-2-pyrrolidinyl)-, (S)-, hexadecen-1-ol, phytol, and docosane were the main identified phytochemical compounds. Our findings demonstrate that tobacco and CBs extracts are effective larvicides and represent eco-friendly alternatives for mosquito control.